Development and internal validation of a prediction model incorporating SOFA, Prognostic Nutritional Index, and Neutrophil-to-Albumin Ratio for early prediction of in-hospital mortality in patients with Sepsis: A single-center retrospective study - Lutian Yi; Tao Yu; Xiaolu Zheng (PLoS ONE, 2026)
Objective Sepsis prognosis is influenced by organ dysfunction, inflammation, and nutritional status. We aimed to develop and internally validate a prediction model incorporating the Sequential Organ Failure Assessment (SOFA) score, prognostic nutritional index (PNI), and neutrophil-to-albumin ratio (NAR) for early risk stratification of in-hospital mortality in patients with sepsis. Methods We conducted a single-center retrospective study of 120 patients with sepsis. A multivariable logistic regression model was developed and internally validated using bootstrap resampling. Model performance was evaluated through discrimination, calibration, and decision curve analysis, with incremental predictive value assessed by net reclassification improvement and integrated discrimination improvement. Results The SOFA score and NAR were independently associated with in-hospital mortality, while PNI did not reach statistical significance in multivariable analysis. The combined model demonstrated good discrimination with an area under the receiver operating characteristic curve of 0.904, higher than SOFA score alone (0.845) and quick SOFA (0.700), although the difference versus SOFA alone was not statistically significant (P = 0.075). Bootstrap internal validation yielded an optimism-corrected AUC of 0.870. Calibration was acceptable (Hosmer-Lemeshow P = 0.057; Brier score = 0.098). Decision curve analysis demonstrated greater net clinical benefit compared with SOFA score alone. The combined model showed potential improvement in risk reclassification (net reclassification improvement = 0.90; integrated discrimination improvement = 0.15; both P < 0.001), although its improvement in discrimination over the SOFA score alone did not reach statistical significance. Conclusions The combined model showed statistically significant improvement in risk reclassification (net reclassification improvement = 0.90; integrated discrimination improvement = 0.15; both P < 0.001), although its improvement in overall discrimination (AUC) over the SOFA score alone did not reach statistical significance (P = 0.075).